New Refrigerant Molecules from Structure Optimization. - Rosero Hidalgo, Cristhian Raúl (2021)
In the present work, various objective function were formulated and optimized using the mixed integer nonlinear programming and the generalized reduced gradient nonlinear method from the solvertoolof Microsoft® Excel 2016, respectively. The CH3FO2, C2H4F2O, CH2F2O2, CH2F2O, C3H4F2, andtheC2H2F2O molecules were found to meet structural feasibility constraints and physical properties from refrigerant molecules and have not previously been reported in the literature. The senew refrigerants present global warming potential values similar to that from the R-134 and Freon 12 refrigerants and null ozone depletion potential. Moreover, these molecules are normally flammable, assimilarasto R-134 a refrigerant. TheCH3FO2, C2H4F2O, CH2F2O2, C2H2F2O, and CH2F2O show toxicity values similarto R-134a and Freon 12 refrigerants.